Pengaruh Penerapan Model Pembelajaran Berbasis Proyek (Poject Based Learning) Pada Materi Fisika Trafo/Transformator Terhadap Hasil Belajar Fisika Siswa Kelas XII Sains Dan Teknologi (Ciência E Tecnologia) Ensino Secundário Geral Publico 05 De Maio Becora - Manuel Lu Fonseca Soares; Maria Lia Felizarda Freitas; Estaquio Amaral (MAGNETON: Jurnal Inovasi Pembelajaran Fisika UNWIRA, 2023)
The purpose of this study was to determine the effect of the application of a project-based learning model on physics material "transformer/transformer" on the learning outcomes of students of class XII SMAN 5 de Maio Becora TP 2022. This type of research in terms of sample data is a type of quantitative research. The sample of this research is the XII grade students of Ensino Secundário Geral Publico 05 de Maio Becora, Díli, Timor-Leste as many as 30 people who are divided into two classes, namely 15 people for the experimental class and 15 people for the control class. The experimental class is a class where in the implementation of the teaching and learning process, the teacher applies a project-based learning model. While the control class is the teacher applying conventional model. The results of data analysis showed that students in the experimental class obtained a t_count value greater than the t_count in the control class, namely 16.362> 3.292. This indicates that the learning outcomes of Physics students in the experimental class are better than the control class. Therefore, it can be concluded that the project-based learning model is very effective in applying the physics material "transformer/transformer" because it can make students active and creative in understanding concepts and principles, able to investigate problems related to and find solutions relevant to physics material, and make students learn independently, to obtain excellent learning outcomes. The results of this study indicate that there is a significant influence on the experimental class with the application of the PjBL-based learning model on the learning outcomes of students of class XII Ensino Secundário Geral Publico 05 Becora Dili, Timor-Leste in the 2022 teaching year